2005
DOI: 10.1111/j.1365-3083.2005.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

IL‐10 Promoter −1082 Polymorphism is Associated with Elevated IL‐10 Levels in Control Subjects but Does not Explain Elevated Plasma IL‐10 Observed in Sjögren's Syndrome in a Hungarian Cohort

Abstract: The aim of this study was to investigate the frequency of the À1082 polymorphism of the interleukin-10 (IL-10) gene and the soluble IL-10 levels in Hungarian primary Sjögren's syndrome (SS) patients. Ninety-nine SS patients and 135 healthy volunteers were examined. Samples were analysed by the PCR restriction fragment length polymorphism method, and IL-10 plasma levels were assesed by a commercial enzyme-linked immunosorbent assay. IL-10 plasma levels were higher in the primary SS patients (36.4 AE 57.5 pg/ml,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…Furthermore, Fox et al suggested that salivary gland CD4+ T cells produce over 40-fold more IL10 mRNA than peripheral blood CD4+ T cells from the same patient or normal controls, moreover, increased levels of IL-10 were found in saliva of pSS patients suggesting that the elevated mRNA levels detected in their glandular tissue correlated with local protein synthesis [49]. Primary Sjögren's syndrome patients also showed increased levels of sIL-10 in concordance with previous reports [2,3,20,24,53] suggesting an important role of this cytokine in the pathogenesis of the disease. The immunostimulatory properties of IL-10 in primary Sjögren's syndrome have been evaluated in mice transgenic for IL-10 in which the mouse IL10 gene was regulated by the human salivary amylase promoter.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, Fox et al suggested that salivary gland CD4+ T cells produce over 40-fold more IL10 mRNA than peripheral blood CD4+ T cells from the same patient or normal controls, moreover, increased levels of IL-10 were found in saliva of pSS patients suggesting that the elevated mRNA levels detected in their glandular tissue correlated with local protein synthesis [49]. Primary Sjögren's syndrome patients also showed increased levels of sIL-10 in concordance with previous reports [2,3,20,24,53] suggesting an important role of this cytokine in the pathogenesis of the disease. The immunostimulatory properties of IL-10 in primary Sjögren's syndrome have been evaluated in mice transgenic for IL-10 in which the mouse IL10 gene was regulated by the human salivary amylase promoter.…”
Section: Discussionsupporting
confidence: 80%
“…In primary Sjögren's syndrome, the IL10 polymorphisms and their haplotypes have been analyzed showing discordant results, -1082 GG and GCC haplotype have been associated as genetic risk factors for pSS in Caucasians [8,20,21], while ATA haplotype has been considered as risk factor in Asians [8,22]. However, some reports in Caucasians have not associated IL10 polymorphisms and haplotypes with susceptibility to pSS [23][24][25].…”
Section: Introductionmentioning
confidence: 94%
“…In previous study, pSS patients who carried the “GCC” haplotype were identified to have a significantly elevated level of plasma IL-10 compared with GCC-negative patients [18]. The patients with GCC haplotype were also confirmed to have an earlier onset of pSS, whereas other investigators could not find the kind of difference [19], [21]. In other study, GCC haplotype was shown to be associated with clinical manifestation of some autoimmune disease.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 9 relevant studies with IL-10, TNF-αgene polymorphisms and susceptibility to pSS were left for final inclusion in the meta-analyses. 7 articles were identified to assess the SNPs within IL-10 gene and pSS [17], [18], [19], [20], [21], [22], one of which also contained the data about TNF-α polymorphisms [23]. Then, the remaining 2 studies focused solely on TNF-α gene polymorphisms [24], [25].…”
Section: Resultsmentioning
confidence: 99%
“…Since the PBMC of only some of the infants in this study spontaneously secreted detectable levels of IL-10 and, consequently, low IFN-␥ concentrations upon stimulation with FHA and PT, we investigated whether these differences could be linked to genetic polymorphisms of the IL-10 gene promoter which have been reported to influence the constitutive IL-10 production (14,24,25).…”
Section: Fha-and Pt-induced Ifn-␥ Secretionsmentioning
confidence: 99%